High-performance nutrition for masters athletes - Antonucci, Lauren A. 1974-
"This book provides current, credible nutrition guidance for athletes who are 35 years old or older. The content-which includes charts, meal plans, and expert interviews-applies across all sports, with emphasis on endurance sports"--Provided by publisher.